Calvinists and Catholics during Holland's golden age heretics and idolaters - Kooi, Christine (Cambridge [England] ; New York : Cambridge University Press, 2012)
"This book examines the social, political and religious relationships between Calvinists and Catholics during Holland's Golden Age. Although Holland, the largest province of the Dutch Republic, was officially Calvinist, its population was one of the most religiously heterogeneous in early modern Europe. The Catholic Church was officially disestablished in the 1570s, yet by the 1620s Catholicism underwent a revival, flourishing in a semi-clandestine private sphere. The book focuses on how Reformed Protestants dealt with this revived Catholicism, arguing that confessional coexistence between Calvinists and Catholics operated within a number of contiguous and overlapping social, political and cultural spaces. The result was a paradox: a society that was at once Calvinist and pluralist. Christine Kooi maps the daily interactions between people of different faiths and examines how religious boundaries were negotiated during an era of tumultuous religious change"--
Machine generated contents note: Introduction; 1. War and peace; 2. Priests and preachers; 3. Persecution and toleration; 4. Converts and apostates; 5. Kith and kin; Conclusion.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Netherlands -- Church history -- 17th century; Calvinism -- Netherlands -- History -- 17th century; Reformed Church -- Netherlands -- History -- 17th century; Catholic Church -- Netherlands -- History -- 17th century; HISTORY / Europe / General; RELIGION / Christianity / History; Electronic books